Technology Role in Knowledge Management - A Case Study on the Saudi Pharmaceutical Industries and Medical Appliances Company SPIMACO - - Alrebdi, Dalal Ibrahim; Alseryhi, Mona Dakeel (Journal of Humanities & Social Sciences, 2020)
The world today is living in the era of technology that has encouraged and revolutionized many fields, including the industrial fields. This revolution has led to an expansion in the business world to lead to the overwhelming use of the latest technological solutions that were discovered all around the world, which therefore has led to intense competition in the local and global markets. The need for industrial organizations to obtain accurate and timely data and information hastily contributes to decision-making and directs work more accurately and with higher quality. Therefore, we see that these industrial organizations that seek to develop, often refine systems thinking through the development of knowledge management and its application depending on its technology. From this standpoint, this study sought to shed light, examine and analyze the role of technology in the application of knowledge management, by choosing the Saudi Pharmaceutical Company, SPIMACO, as a model for industrial companies, to apply this study by polling a number of company employees، the study followed the survey approach, where the survey and interview tools were used. The entire study population consisted of (1223) employees, (320) were selected as a sample of the study. The research reached a determination of the role of technology in the application of knowledge management in industrial companies, as it was found that the degree of availability of technical indicators supporting the application of knowledge management in this pharmaceutical company is of 'high' availability. The study also came out with a number of recommendations, the most prominent of which was the continuation of the implementation of technical systems that allow the company’s management to communicate internal knowledge, plan and execute tasks easily that helps in extracting and circulating knowledge and improving the current situation of the reality of employing the technical systems that are used in the process of measuring cognitive performance.
Keywords: technology; application of knowledge management; industrial companies; Saudi pharmaceutical company Spimaco; SPIMACO